PERBANDINGAN MINAT BELAJAR TINGGI DENGAN MINAT BELAJAR RENDAH TERHADAP HASIL BELAJAR BATIK SISWA PROGRAM KEAHLIAN KRIYA TEKSTIL SMK NEGERI 8 PADANG - Drs. Yusron Wikarya, M.Pd., DITRI MAYANG SARI, Drs. Eswendi, M.Pd., (Jurusan Seni Rupa FBS UNP Padang, 2017)
This study aims to determine the ratio of interest in learning based on the results of batik students learning Craft Programs Textiles SMK Negeri 8 Padang. The hypotheses tested in this study are: There is a difference in interest in learning based on the results of batik students learning Craft Programs Textiles SMK Negeri 8 Padang. The type of this research is kuntitatif research by using comparative research. Quantitative research model with descriptive research method. Sampling technique purposive sampling on students in SMK Negeri 8 Padang. The class chosen in this research is class XI Kriya Tekstil. Collection of data results is done through the division of questionnaires and student learning outcomes in teacher value books. The processing stages of analysis use normality test, homogeneity test, and hypothesis test by using independent sample.The results obtained tcount of 11.211 ttable 1.662 and significance of 0.00. The result of analysis shows that the value of Sig (0,00) <(0,05), so H0 is rejected and Ha accepted. This means that there are significant differences in student learning interests based on the results of batik students learning Crafts Program Textile Craft SMK Negeri 8 Padang.Keywords: Interest in learning, learning outcomes, batik, and textile crafts